The TanDEM-X Mission Design and Data Acquisition Plan - Fiedler, Hauke; Krieger, Gerhard; Werner, Marian; Reiniger, Klaus; Eineder, Michael; D'Amico, Simone; Diedrich, Erhard; Wickler, Martin (European Conference on Synthetic Aperture Radar (EUSAR), 2006)
The TanDEM-X mission comprises two fully active synthetic aperture radar Xband satellites, operating three years as a joint mission. The primary goal of this mission is the derivation of a high-precision global DEM according to HRTI level 3 quality. Also secondary mission goals shall be performed like e.g. digital beam-forming, along-track interferometry or bi-static experiments. The orbit control is based on the HELIX principle, an e/i-vector separation of the two satellites, enabling a safe and collision free operation of the spacecrafts. This formation is highly reconfigurable and allows many kinds of applications. To achieve the primary goal, a data acquisition strategy is derived, which proves the feasibility of a single global mapping of the Earth in approximately 1½ years. This strategy works as a reference scenario, which specifies for each orbit different possible data acquisitions at various latitudes with several incident angles. This is necessary to avoid data acquisition conflicts with the original TerraSAR-X mission. It is envisaged that each satellite covers 50 percent of the already planned TerraSAR-X mission, leaving enough monitoring time for the joint mission. For deriving such a highly accurate DEM, it is prerequisite that the baselines and their corresponding height of ambiguities correspond to the requirements of the HRTI-3 standard. Therefore, as the baselines vary with latitude and incident angle, the formation shall be adjusted such that each scene is monitored with an optimum baseline. Due to topographic influences, one data acquisition might not suffice for terrain with steep gradients; for such regions, additional monitoring time is allocated in a second mission phase. For these additional data acquisitions, the formation is reconfigured. This second phase will last approximately one year, leaving enough time in this three year mission scenario for a third phase to allow for secondary mission goals like e.g. along-track interferometry, bi-static mapping or digital beamforming. For this whole scenario, the total fuel consumption is estimated taking into account relative orbit control, manoeuvre budget for formation control, and formation reconfiguration. Finally, a brief data reception concept is presented which allows for sufficient downlink capacity with a network of ground stations. Furthermore, a data processing system is presented which is compatible with already existing structures developed for the TerraSARX mission. A modular processing chain is introduced, which allows the handling of a large amount of data (based on developments from SRTM and TerraSAR-X), bi-static imaging, multi-baseline interferometry, global calibration, precision mosaicking, and data archiving.
DLR Import::2019-04-03